A QOS Evaluation of the TCP Congestion Control Algorithm - Mnaathr, Satar Habib (2010)
Networking evaluation techniques have been carried out different procedures and behavior for presenting the TCP/IP state over different areas. Furthermore, the rapid growth of using quality of services technique (QoS) for measuring and monitoring the TCP/IP state has growth rapidly due to the improvement process for presenting new techniques over LAN. TCP congestion algorithm has been used to control and monitor the TCP/IP state over local area network. Different difficulties have been presented the integration or the using of first in-first out technique among router for scheduling TCP/IP state. Hence, this study has been concerned on using the quality of service evaluation process of the TCP cognition control algorithm and to measure the TCP cognition control algorithm state over local area network by deploying QCheck system. However, Object Oriented Approach Modified (Hoffer, 1999) has been employed for deploying QCheck system over LAN, development, and testing the deployed system (QCheck) over LAN.